Genomic signatures of SnRKs highlighted conserved evolution within orchids and stress responses through ABA signaling in the Cymbidium ensifolium - Ruiyue Zheng; Kai Zhao; Jiemin Chen; Xuanyi Zhu; Yukun Peng; Mingli Shen; Zhong-Jian Liu; Donghui Peng; Yuzhen Zhou (BMC Plant Biology, 2025)
Abstract Sucrose non-fermenting 1-related protein kinases (SnRKs) are crucial for modulating plant responses to abiotic stresses, linking metabolism with stress signaling pathways. Investigating the roles and stress responses of SnRKs in plants paves the way for developing stress-tolerant strategies in orchid species. Here, 362 SnRK members were identified from nine current orchid genomes, highlighting the conservation of these genes in evolution. Among these, 33 CeSnRKs were found across 20 chromosomes of C. ensifolium genome. Multiple duplication events increased the complexity of CeSnRKs during independent evolution. Moreover, distinct functional domains beyond the kinase domain differentiated the subfamilies. These multi-copy members existed tissue specific expressions falling into 6 main trends, especially CeSnRK1, CeCIPK9, CeCIPK23 displayed a strict floral expression. ABA-related elements were enriched in the promoters of CeSnRKs, and stress-related miRNA binding sites were identified on partial CeSnRKs. Consequently, most CeSnRKs exhibited up-regulated expression during ABA treatment. Several genes, such as CeSnRK2.1 and CeCIPK28 involved growth and development at different times and various tissues. The up-regulation of SnRK2.1, along with high expression of SnRK1 and CIPK27 under drought stress, and the differential expression patterns of CeSnRKs under cold stress, underscore the involvement of CeSnRK genes in different stress responses. Additionally, the diverse interactions of CeSnRKs with proteins highlighted a multifaceted functional network.These findings offer valuable insights for the future functional characterization formation of CeSnRKs and the adaptive evolution of genes in orchids.